MEMS GC Column Performance for Analyzing Organics and Biological Molecules for Future Landed Planetary Missions - Blase, Ryan C.; Libardoni, Mark J.; Miller, Gregory P.; Miller, Kelly E.; Phillips-Lander, Charity M.; Glein, Christopher R.; Waite, J. Hunter; Ghosh, Abhishek; Venkatasubramanian, Anandram; Li, Maxwell Wei-hao; Stephens, Andrew; Fan, Xudong; et al. (Frontiers in Astronomy and Space Sciences, 2022)
We present a novel, innovative approach to gas chromatography-mass spectrometry (GC-MS) based on micro-electro-mechanical systems (MEMS) columns that improve the current, state-of-the-art by dramatically reducing the size, mass, and power resources for deploying GC for future landed missions. The outlet of the MEMS GC column was coupled to a prototype of the MAss Spectrometer for Planetary EXploration (MASPEX) through a heated transfer line into the ion source. MEMS GC-MS experiments were performed to demonstrate linearity of response and establish limit of detection (LOD) to alkanes (organics), fatty acid methyl esters (FAMEs) and chemically derivatized amino acids (biological molecules). Linearity of response to each chemical family was demonstrated over 2 orders of magnitude dynamic range and limit of detection (LOD) values were single to tens (4 - 43) of picomoles per 1 μL injection volume. MEMS GC column analytical performance was also demonstrated for a “Mega Mix” of chemical analytes including organics and biological molecules. Chromatographic resolution exceeded 200, retention time reproducibility was <<1% RSD (majority ≤ 0.3%), and peak capacity values calculated to be 124 ± 2 over a 435 s retention time window. The 5.5 m MEMS column was also shown to be a suitable alternative to traditional commercial columns for use in comprehensive two-dimensional gas chromatography (GC×GC). Mass spectra collected from MASPEX showed close consistency with National Institute of Technology (NIST) reference mass spectra and were used for high confidence identification of all eluting analytes.